INTERNALISASI NILAI-NILAI PENDIDIKAN SURAU SEBAGAI DAYA TANGKAL RADIKALISME DI SUMATERA BARAT - Muspardi Muspardi (Universitas Sriwijaya, 2020)
Internalization of Surau Education Values is one of the efforts that can be done for preventing radicalism in West Sumatra.West Sumatra is a province that has famous people who have moderate, open minded and tolerant diversity.Therefore, this study aims to explore the Surau education values in the perspective of religious leaders, customs and Minangkabau intellectual.This research uses a qualitative approach with descriptive methods. Data collection techniques through interviews, observation, and study documentationThe results of this study reveal that the values of Surau education values which are usually internalized to students consist of the following four categories : First, the value of the heart consists of pure tauhid to Allah SWT, honest, true and sincere worship and responsible; Second, the value of feeling consist of continuity, wise communication, mutual love and respect for all elements of society, egalitarian and good at adjusting wherever they are. Third, the value of thought consists of critical, intelligent, creative, innovative, visionary, and open-minded;Fourth, the value of sports consists of strong, tough, disciplined, independent, capable and brave in defending themselves and defending the truth.The values of the surau education above can be internalized in the education of families, schools and communities with approaches that need to be contextualized in accordance with the current development for preventing radicalism in West Sumatra.